Effect of service quality and price perception on customer satisfaction at kedai bedikari rembang - Ahmad Rizal Rahardian; Alimuddin Rizal (International Journal on Social Science, Economics and Art, 2025)
In Indonesia, the development of restaurants and eateries indicates a progressively intensifying competition within the culinary industry. In this context, consumers are increasingly focused on the satisfaction they derive from their dining experiences. As a result, it it essential for culinary entrepreneurs to carefully consider and improve strategies that effectively address consumer needs. The purpose of this study is aimed to analyze the service quality impact and price perception on consumer satisfaction. The population taken was consumers of Kedai Bedikari Rembang. The sample collection technique used accidental sampling technique and purposive sampling technique as many as 100 respondents. This study uses quantitative analysis with validity test, reliability test, normality test, classical assumption test, correlation coefficient, determination coefficient, multiple regression analysis, and significance test (t test and F test) with SPSS Software application version 22 The study's findings suggest that both service quality and price perception exert a positive and significant influence on consumer satisfaction.